Unified and rapid assessment of climate resilience of urban drainage system by means of resilience profile graphs for synthetic and real (persistent) rains. (1st October 2019) - Wang, Sheng; Fu, Jia; Wang, Heng
Abstract: Urban drainage system (UDS) researchers have applied the concept of resilience for minimizing the magnitude and duration of urban flooding in response to climate change. Currently, the relationship between conventional design and resilience analysis still remains unknown, while persistent rain has not been included in resilience assessment. The present study proposes new metrics by means of resilience profile graph for UDS stressed by synthetic short-duration storms and real persistent rains. The graph unifies the concepts of reliability, robustness, resilience and failure, as well as design standards for sewer surcharging, sewer flooding and property flooding, which are linked into curves to show a complete performance under climate stress scenarios. The obtained results show that resilience profile curves for short-duration storms are well fitted by power functions with coefficient of determination 98.13%–99.9%. Chicago hyetograph was used as critical input hyetograph where the error range was −0.34%–6.83% compared with actual hyetograph. Resilience profile graphs for persistent rains reveal that resilience assessment based on short-duration storms underestimates the effect of persistent rains, and it can be obtained by using segmental and reference reliability metrics to reduce working time from weeks to hours. For the rain of the same intensity, resilience to persistent rain was 18.4–33.1% lower than for single rains. Threat of persistent rain doesn't fall under the rains of high intensity but under large rainfall in total (which exceeds 25% of local annual rainfall), while re-planning water landscape as retarding basin reduces the impact of persistent rains to 5.8–11.8%. Graphical abstract: Image 1 Highlights: A single graph incorporates design standards, reliability, robustness, resilience and failure. Design standards (shown by points) are linked into curve to show a complete performance. Resilience profile curves for short-duration single rains are well fitted by power functions. For the rain of the same intensity, resilience to persistent rain is lower than for single rains.